2022
DOI: 10.1111/cch.12973
|View full text |Cite
|
Sign up to set email alerts
|

WeChat‐based remote follow‐up management alleviates the home care burden and anxiety of parents of premature infants: Randomized controlled study

Abstract: Objective The purpose of this study was to explore the effect of WeChat‐based remote follow‐up management on reducing the home care burden and anxiety of parents of premature infants. Methods A randomized controlled study was conducted in our hospital, with 150 premature infants enrolled in this study, each with 75 cases in the intervention group and the control group. WeChat‐based remote follow‐up management was performed in the intervention group after discharge, while traditional outpatient follow‐up manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…In this study, we found that the FCTI scores (31.79 ± 3.33 and 31.10 ± 4.21) and ZBI scores (51.97 ± 3.90 and 51.00 ± 4.34) at discharge of the 2 groups indicated that the parents of children with epilepsy faced a heavy burden of family care. [18] Moreover, results of the present study also showed that the SAS scores and SDS scores of the parents of the children with epilepsy were (59.26 ± 4.73 and 59.51 ± 5.04) and (58.07 ± 4.83 and 57.43 ± 4.38), respectively. According to the interpretation of the SAS scale and the SDS scale, that is, SAS score >50 indicates anxiety [27] and SDS score higher than 40 indicates depression, [28] and parents of children with epilepsy in both groups have different degrees of anxiety and depression at the time of discharge.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…In this study, we found that the FCTI scores (31.79 ± 3.33 and 31.10 ± 4.21) and ZBI scores (51.97 ± 3.90 and 51.00 ± 4.34) at discharge of the 2 groups indicated that the parents of children with epilepsy faced a heavy burden of family care. [18] Moreover, results of the present study also showed that the SAS scores and SDS scores of the parents of the children with epilepsy were (59.26 ± 4.73 and 59.51 ± 5.04) and (58.07 ± 4.83 and 57.43 ± 4.38), respectively. According to the interpretation of the SAS scale and the SDS scale, that is, SAS score >50 indicates anxiety [27] and SDS score higher than 40 indicates depression, [28] and parents of children with epilepsy in both groups have different degrees of anxiety and depression at the time of discharge.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, all parents of recruited epileptic children were informed of the detailed agreement of this study and their rights and obligations, and all of them signed informed consent form. Based on the data from our previous study [18] and assuming that the alpha value was set at 0.05 with a power of 0.9, the required number of participants was calculated to be 68 in each group. Assuming a 10% missing rate, the total sample size was set as at least 150, each with 75 cases at least in the intervention group and the control group.…”
Section: Ethical Statement and Sample Size Calculationmentioning
confidence: 99%
See 2 more Smart Citations
“…We assessed the effects of DMH intervention compared with control groups with a mean (SD) from 80 studies (67 records for depression and 65 records for anxiety; Figure 2 [ 26 , 28 , 29 , 32 , 33 , 35 - 39 , 44 - 47 , 54 , 55 , 57 , 59 - 61 , 63 , 65 , 68 - 78 , 80 , 82 - 84 , 86 - 88 , 90 , 91 , 93 , 95 , 97 - 101 , 106 , 107 , 109 , 111 , 113 , 115 , 117 , 119 - 121 ] and Figure 3 [ 27 , 29 , 30 , 32 , 35 - 38 , 40 , 42 , 43 , 48 - 50 , 52 , 55 - 59 , 61 , 62 , 68 , 69 , 72 - 74 , 78 , 80 , 82 - 84 , 86 , 88 , 89 , ...…”
Section: Resultsmentioning
confidence: 99%